Steeper Delay Discounting for Potentially Real versus Hypothetical Cigarettes (but not Money) in Czech Republic Smokers. - Lawyer, Steven R.; Prihodova, Tereza; Prihodova, Katerina; Rasmussen, Erin; Doubkova, Nikola; Preiss, Marek (Psychological Record, 2022)
A relatively large literature suggests that hypothetical and potentially real monetary rewards yield similar patterns of responses in delay (DD) and probability (PD) discounting. However, the much smaller literature concerning hypothetical versus potentially real cigarettes is more mixed and the generalizability of findings from both of these literatures outside the United States is unclear. The present study extended research comparing hypothetical and potentially real delayed and probabilistic monetary and cigarette outcomes to adult smokers (N = 59) in the Czech Republic using a within-subjects design. Comparison of hypothetical versus potentially real outcomes across tasks revealed Czech smokers discounted the value of potentially real cigarettes (but not money) more steeply than hypothetical cigarettes on the DD, but not PD, task. Findings also suggest a gender effect in which male participants discounted the value of money and cigarette outcomes more than did women for DD (but not PD). The relevance to methodological factors, cultural factors, and gender effects in discounting are discussed.